Student’s Creativity Profile with Base on Thinking Model for Physics Problem Solving - Hartono Bacong; Subaer S (Department of Physics, Sebelas Maret University, 2015)
A research that aims to determine the profile of student’s creative who have a concrete sequential thinking styles, sequential abstract, concrete random, and abstract random in solving physics problems at the State University of Makassar. This study is a qualitative research. The sample was taken by using purposive random sampling technique. The data obtained were analyzed using Miles and Hubermann model. The results describe creativity of student thinking style in solving physics problems. The conclusion shows that the concrete sequential of thinking’s style